Modulation of Neuronal Damage in DRG by Asprosin in a High-Glucose Environment and Its Impact on miRNA181-a Expression in Diabetic DRG - Adam, Muhammed; Ozcan, Sibel; Dalkilic, Semih; Tektemur, Nalan Kaya; Tekin, Suat; Bilgin, Batuhan; Ozcan, Mete (Springer, 2024)
Asprosin, a hormone secreted from adipose tissue, has been implicated in the modulation of cell viability. Current studies suggest that neurological impairments are increased in individuals with obesity-linked diabetes, likely due to the presence of excess adipose tissue, but the precise molecular mechanism behind this association remains poorly understood. In this study, our hypothesis that asprosin has the potential to mitigate neuronal damage in a high glucose (HG) environment while also regulating the expression of microRNA (miRNA)-181a, which is involved in critical biological processes such as cellular survival, apoptosis, and autophagy. To investigate this, dorsal root ganglion (DRG) neurons were exposed to asprosin in a HG (45 mmol/L) environment for 24 hours, with a focus on the role of the protein kinase A (PKA) pathway. Expression of miRNA-181a was measured by using real-time polymerase chain reaction (RT-PCR) in diabetic DRG. Our findings revealed a decline in cell viability and an upregulation of apoptosis under HG conditions. However, pretreatment with asprosin in sensory neurons effectively improved cell viability and reduced apoptosis by activating the PKA pathway. Furthermore, we observed that asprosin modulated the expression of miRNA-181a in diabetic DRG. Our study demonstrates that asprosin has the potential to protect DRG neurons from HG-induced damage while influencing miRNA-181a expression in diabetic DRG. These findings provide valuable insights for the development of clinical interventions targeting neurotoxicity in diabetes, with asprosin emerging as a promising therapeutic target for managing neurological complications in affected individuals.
Keywords: Asprosin; Diabetes; Cell viability; Apoptosis; Dorsal root ganglion; miRNA-181a